The Latin America’s far-right swarm - Ubilluz, Juan Carlos (2024)
This text presents the main themes of the dossier The Latin American Far Right Today: the politics of the far-right at the national level; the history, narratives, strategies and conditions of production of cultural battle; the struggles of the so-called ‘gender ideology’; and the relations of the far right with an authoritarian, negationist, non-democratic tradition. The articles presented here study the multiple singularities of the far right, but also examine how these are not hierarchically organized around a party, but rather have a decentered and networked structure that Hardt & Negri (2004, 2017) identified with the democratic and progressive movements that emerged at the beginning of the 21st century. In other words, the far right operates as a multitude or a swarm that paradoxically advances towards an authoritarian and conservative populism. On the other hand, this introduction also interrogates the historical matrix from which the Latin American far right starts in its quest to reestablish or recreate a conservative social order. Unlike the European far-right, which according to some authors has classical fascism as its referent, the current Latin American far-right refers to the military regimes that were established between the 1960s and 1980s. It is from this place that the far right is interested in confronting dissidence with an “heavy handed” in order to impose a development model based on economic neoliberalism and social conservatism.